The Art of Saying "No" to University Students: A Pragmatic Analysis of the Speech Act of Refusal in Teacher-Student Role-Plays - Dina Abdel Salam El-Dakhs (National Research University Higher School of Economics, 2020)
The current study aimed to investigate how university teachers decline students' requests. To this end, the realization strategies of the speech act of refusal by 60 faculty members at a private Saudi university were examined. Data were collected through role-plays and were coded by using an adapted version of Beebe, Takahashi and Uliss-Weltz's (1990) model of refusal strategies and an adapted version of Trosborg's (1995) model of internal modifiers. The results showed a clear preference for indirect strategies, a limited use of modifiers, particularly internal ones, and a minimal influence for gender and the teaching experience on the realization strategies. The results are interpreted in light of Brown and Levinson's (1978, 1987) politeness theory, the use of English as a lingua franca, the specific context of teacher-student talk and the existing literature.